Examining growth centers and agricultural base commodities to enhance regional development in Tanjung Jabung Barat Regency, Jambi Province - Erni Achmad; Zamzami Zamzami; Nurul Hariza; I Wayan Suparta; Sony Tian Dhora (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2023)
Determining growth centers and agricultural base commodities is essential for optimizing economic development and achieving economic equality in the Tanjung Jabung Barat Regency area. This study aimed to identify sub-districts that could become growth centers, establish agricultural commodities based in each Tanjung Jabung Barat Regency sub-district, and examine interactions between growth centers and surrounding areas. Three methods employed in this research include Scalogram analysis, Centrality Index, Location Quotient, and Dynamic Location Quotient. Based on the Scalogram analysis and Centrality Index results for the 13 Tanjung Jabung Barat Regency sub-districts, four sub-districts were identified as potential growth centers: Tungkal Ilir, Tebing Tinggi, and Merlung. The Tanjung Jabung Barat Regency Government is recommended to establish basic commodity specialization in each sub-district and strengthen inter-regional linkages to accelerate regional economic equity.